Intense anticyclones at the global Argentine Basin array of the Ocean Observatory Initiative - C. Artana; C. Artana; C. Artana; C. Provost (Ocean Science, 2023)
We analyzed physical oceanic parameters gathered by a mooring array at mesoscale spatial sampling deployed in the Argentine Basin within the Ocean Observatory Initiative, a National Science Foundation major research facility. The array was maintained at 42∘ S and 42∘ W, a historically sparsely sampled region with small ocean variability, over 34 months from March 2015 to January 2018. The data documented four anticyclonic extreme-structure events in 2016. The four anticyclonic structures had different characteristics (size, vertical extension, origin, lifetime and Rossby number). They all featured near-inertial waves (NIWs) trapped at depth and low Richardson values well below the mixed layer. Low Richardson values suggest favorable conditions for mixing. The anticyclonic features likely act as mixing structures at the pycnocline, bringing heat and salt from the South Atlantic Central Water to the Antarctic Intermediate Waters. The intense structures were unique in the 29-year-long satellite altimetry record at the mooring site. The Argentine Basin is populated with many anticyclones, and mixing associated with trapped NIWs probably plays an important role in setting up the upper-water-mass characteristics in the basin.